Utilizing “traders” board game to improve entrepreneurship factors among teenagers: a qualitative study - Kususanto, Prihadi (Penerbit Universiti Kebangsaan Malaysia, 2015)
This qualitative study aims to explore the changes of six elements of entrepreneurship (EE) among teenagers after they played an educational board game called Traders of Antrapre (“Traders”). The six elements are namely (1) self-esteem, (2) competitive traits, (3) resilience, (4) self-efficacy, (5) practical intelligence and (6) experience. These elements have been reported as significant contributors to opportunity pursuing skills, which can also be defined as entrepreneurship skills. Moreover, two entrepreneurship styles, namely Kirnzerian (explorative) and Schumpeterian (creative-innovative) were reported to be significantly affected by the six EEs. 12 participants between 11 to 15 years old were briefed and asked to play the board game twice every week for four consecutive weeks, and their in-game behavior were video-recorded and observed. The qualitative data was analyzed in two cycles, namely in vivo and thematic analyses. It was discovered that the more the subjects played the game, the more they showed more adequacy in the six EEs. More importantly, findings of this explorative study led to the hypothesized interrelationship among the EEs as follows: experience influences self-esteem, competitive traits, resilience, and self-efficacy; however, its influence is mediated by practical intelligence. Suggestion to conduct quantitative studies in this subject is presented at the end of this paper.